2020
DOI: 10.1002/jcla.23533
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the specificity of rheumatoid factor detected by latex fixation with that of regulatory rheumatoid factor

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…[42][43][44] On the other hand, the association of DAS-28 and VLDL-C levels is not clear yet, but it has been reported that RA patients with high disease activity had alterations of the lipid profile. 38,45 Rheumatoid factor (RF) correlated with age and smoking index, which agrees with other reports [46][47][48] ; likewise, RF correlated with triglycerides, which could be explained by this autoantibody´s positive correlation with a high RA disease activity, 49 a status associated with lipids alteration.…”
Section: Discussionsupporting
confidence: 89%
“…[42][43][44] On the other hand, the association of DAS-28 and VLDL-C levels is not clear yet, but it has been reported that RA patients with high disease activity had alterations of the lipid profile. 38,45 Rheumatoid factor (RF) correlated with age and smoking index, which agrees with other reports [46][47][48] ; likewise, RF correlated with triglycerides, which could be explained by this autoantibody´s positive correlation with a high RA disease activity, 49 a status associated with lipids alteration.…”
Section: Discussionsupporting
confidence: 89%
“…Previously we found that in RA patients the RF latex test detects at least two RF populations that differ in their specificity and characteristics. 9 One of them is regRF, which is an immunoregulatory factor in the healthy state. The other population, which is not detected in healthy subjects, is specific to lyophilized IgG.…”
Section: Resultsmentioning
confidence: 99%
“… 9 Furthermore, the method of agglutination of tanned IgG‐loaded erythrocytes was shown to detect regRF specifically, while the latex test used to detect RF in RA patients detected both regRF and RA‐associated RF, the latter of which is not detected in healthy subjects. 9 …”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations